ANALISIS MAKNA ASOSIATIF DALAM ALBUM TUTUR BATIN KARYA YUNITA RACHMAN - Nurhidayah, Ghina; Tarmini, Wini (LPPM Universitas PGRI Silampari Lubuklinggau, 2023)
As the meanings continue to expand, there are various changes in meanings across different categories, one of which is associative meaning. Associative meaning refers to the meaning that a word carries, which is related to external circumstances beyond the language itself. The objective of this research is to identify the types of associative meanings in song lyrics, including (1) connotative meaning, (2) stylistic meaning, (3) affective meaning, (4) collocative meaning, and (5) reflective meaning. The research method employed is qualitative descriptive, and data collection techniques include observation and note-taking. The data used in this study consists of the lyrics from the album